2019
DOI: 10.32604/cmes.2019.05666
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of Rectangular and Circular Reinforced Concrete Columns Under Biaxial Multiple Excitation

Abstract: The aim of this study is to investigate the dynamic performance of rectangular and circular reinforced concrete (RC) columns considering biaxial multiple excitations. For this purpose, an advanced nonlinear finite element model which can simulate various features of cyclic degradation in material and structural components is used. The implemented nonlinear fiber beam-column model accounts for inelastic buckling and low-cycle fatigue degradation of longitudinal reinforcement and can simulate multiple failure mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Fatigue load can be divided into low cycle fatigue and high cycle fatigue loads according to the number of load cycles. The low cycle hysteretic behavior of structures under seismic loads has been easily obtained using the general damage model [90][91][92] or the construction of the hysteretic constitutive model [93][94][95]. This section pays attention to the models for concrete structures under high-cycle fatigue loads.…”
Section: Damage Mechanics-based Fatigue Modelsmentioning
confidence: 99%
“…Fatigue load can be divided into low cycle fatigue and high cycle fatigue loads according to the number of load cycles. The low cycle hysteretic behavior of structures under seismic loads has been easily obtained using the general damage model [90][91][92] or the construction of the hysteretic constitutive model [93][94][95]. This section pays attention to the models for concrete structures under high-cycle fatigue loads.…”
Section: Damage Mechanics-based Fatigue Modelsmentioning
confidence: 99%
“…Tey found that multiple excitations due to aftershocks can increase the damage of RC columns, and longitudinal reinforcements signifcantly afect the low-cycle fatigue. Furthermore, it was concluded that the rectangular column is more sensitive to accumulative damage due to cyclic fatigue [7].…”
Section: Introductionmentioning
confidence: 99%
“…Sequential seismic events have caused tremendous economic losses and life safety threat in recent years (the 2008 Wenchuan earthquake; the 2011 Tohoku earthquake; the 2016 central Italy earthquake). Concerns about seismic behaviour of structures under the excitation mainshock-aftershock (MSAS) have been raised [1,2]. In performance-based seismic design, drift ratio is the most commonly used engineering demand parameter (EDP) to predict the seismic performance of structures.…”
Section: Introductionmentioning
confidence: 99%
“…In performance-based seismic design, a precise structural model is crucial. Many investigations have been done to explore the adaption of numerical models of RC bridge piers [2,10,19, 18]. Lumped-plasticity element, distributed inelasticity element with force-based formulation and distributed inelasticity element with displacement-based formulation are most commonly used modelling strategies.…”
Section: Introductionmentioning
confidence: 99%